2014
DOI: 10.1111/isqu.12116
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation or Confrontation? Explaining Differences in Policies Toward Iran

Abstract: Even though democracies by and large share the perception of Iran as a threat to peace and security, they disagree over the appropriate policy response. This paper examines why some democracies prefer accommodation while others plead for confrontation. Using a new data set on democracies' policies toward Iran in the 2000s, we assess the impact of power positions, commercial interests, and domestic political cultures while controlling for government ideology. While we find little support for any impact of power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The result also confirms previous research by Liberman (, ) and Onderco and Wagner (). Wagner and Onderco () also found that domestic punitivity is related to the likelihood of support for punitive action internationally. While the survey data do not permit further analysis, the result underlines the need for further research into individuals’ drivers of punitivity in Europe, where research is still in its infancy.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The result also confirms previous research by Liberman (, ) and Onderco and Wagner (). Wagner and Onderco () also found that domestic punitivity is related to the likelihood of support for punitive action internationally. While the survey data do not permit further analysis, the result underlines the need for further research into individuals’ drivers of punitivity in Europe, where research is still in its infancy.…”
Section: Resultsmentioning
confidence: 95%
“…Previous research has shown that countries with punitive domestic criminal systems are more likely to be confrontationist towards countries breaking international norms (Wagner ; Wagner & Onderco ), and that democracies still exercising the death penalty are more likely to engage in militarised interstate disputes (Stein ). Similarly, support for the death penalty has been associated with higher support for war in Iraq or for the torture of terrorism suspects (Liberman , , ).…”
Section: Ideational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have examined the role of commercial interests on policies towards norm violations in a prior study on Iran, seeWagner and Onderco (2014). The ideational foundations of coercion 283 https:/www.cambridge.org/core/terms.…”
mentioning
confidence: 99%
“… 3 We have examined the role of commercial interests on policies towards norm violations in a prior study on Iran, see Wagner and Onderco (2014). …”
mentioning
confidence: 99%